P5_8 Is Human Hair the Future? - Ruprai, Amrik; Agrawal, Rusi; Shaikh, Hasan; Singh, Jagraj (Physics Special Topics, 2021)
The contents of this paper involve the study of human hair and its potential useful application in modern life with a focus on its thermal and tensile properties . It was found that the power generated by daily natural hair loss was 5.14 × 7 kW/h and that the force a single strand of hair could carry without snapping in ideal conditions was 5.47 × 10−3 N.